Comparison of the Classical Test Theory and the Rasch Model in the Analysis of Mastery Test of Concept Systems of Linear (SPLDV) - Ciptari, Putu Aulia; Purwanti, Ni Kadek Rini; Erawati, Ni Ketut (FKIP Universitas Muhammadiyah Tangerang, 2024)
This study aims to compare the analysis of the quality of a measurement instrument for concept understanding using the classical test theory approach and the Rasch model. The analysis methods for instrument quality, including validity, reliability, item difficulty, and item discrimination, were applied to the SPLDV concept mastery instrument. The research findings reveal differences in the instrument quality between the two approaches. The analysis through the classical test theory approach shows good instrument quality regarding validity and reliability, although item difficulty still needs improvement. On the other hand, the analysis through the Rasch model shows variation in item difficulty and sufficient reliability. While the item discrimination through the classical test theory approach is categorized as good, the analysis through the Rasch model yields unsatisfactory results. In conclusion, the quality of the instrument can differ depending on the approach used. This study provides a better understanding of the differences between the classical test theory approach and the Rasch model in analyzing the quality of a measurement instrument for conceptual understanding.